2010
DOI: 10.1055/s-0037-1619063
|View full text |Cite
|
Sign up to set email alerts
|

Hämophilie A und Hämophilie B

Abstract: SummaryHaemophilia B (HB) was described in 1952 as a single disease for the first time. In comparison to haemophilia A (HA) the bleeding tendency seemed to be less severe. The aim of this study was to investigate this hypothesis in all patients with HA and HB treated in the haemophilia care center of the Vivantes Klinikum. Patients, methods: All patients with severe HA and HB treated at the haemophilia care center were included. We evaluated the regimen of replacement therapy and factor concentrate consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Those studies have demonstrated a high level of genotypic diversity within and between poplar populations based on microsatellite markers. Furthermore, microsatellite clones (Schroeder and Fladung, 2010;Orlović et al, 2009) and to examine their transferability (Bruegmann and Fladung, 2013). According to these previous studies, the microsatellite marker analysis appeared to be the most appropriate for calculating gene diversity and tracing identical genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Those studies have demonstrated a high level of genotypic diversity within and between poplar populations based on microsatellite markers. Furthermore, microsatellite clones (Schroeder and Fladung, 2010;Orlović et al, 2009) and to examine their transferability (Bruegmann and Fladung, 2013). According to these previous studies, the microsatellite marker analysis appeared to be the most appropriate for calculating gene diversity and tracing identical genotypes.…”
Section: Introductionmentioning
confidence: 99%